Música e movimento corporal no contexto da educação física adaptada: um estudo na APAE de Tocantinópolis - Souza, Tiago De Oliveira (Universidade Federal do Tocantins, 2023)
The study aims to understand the relationship between music and body movement in the development of students at APAE in Tocantinópolis -TO. Documentary research was carried out involving: Pedagogical Political Project - school PPP; reports from the leading teachers, support professionals and the Physical Education teacher from the year 2022. The results demonstrate that musical interventions are used in the daily life of the school as a pedagogical strategy in regular classes, associated with curricular content in recreational activities, at festive events, institutional and dance festivals. The body practices worked on are Dance, Athletics, Futsal and Swimming. Music and body movement are associated, mainly, in Dance activities. It is concluded that the relationship between music and body movement energizes regular and Physical Education classes, bringing benefits to the motor, cognitive and psychosocial development of students.